LIGHT-OFF BEHAVIOR OF CATALYTIC-CONVERTERS - Please, C; Hagan, P; Schwendeman, D (1994)
This paper studies a system of partial differential equations modeling the behavior of an automotive catalytic converter. The particular phenomenon considered in detail is light-off, when the temperature of the converter changes dramatically from cold to hot somewhere within the converter. The initial position of light-off and the subsequent movement of this steep jump in temperature toward the inlet of the converter are analyzed. The method of matched asymptotic expansions is used to study light-off and to derive approximate formulas that determine its behavior in the limits of small heat diffusion and large activation energy. Numerical calculations are presented and are used to compare with the analytical formulas. These calculations reveal that the asymptotic results for small diffusion are quantitatively accurate, while those for small diffusion and large activation energy give the qualitative behavior of the solution but give poor quantitative predictions for the range of parameters encountered in practice.